Rational Emotive Behaviour Counseling Guideline for Academic Resilience in College Students - Galuh Adji Pratama; Mazidah Mohd Dagang; Gian Sugiana Sugara (POTENSI : Journal of Education and Human Development, 2025)
The transition from high school to college often introduces significant stress due to the need to adapt to a new academic culture and social environment. This stress can lead to decreased academic success, lower grades, and even dropout if not managed properly. Challenges such as high academic demands, fatigue, and procrastination hinder student progress. Academic procrastination, influenced by external factors, is linked to various adaptation levels. Beyond intellectual ability, factors such as interest, motivation, and self-concept play crucial roles in academic performance. Students with clear goals and self-management skills are more likely to succeed. Grit which combines resilience, courage, and determination, enhances the ability to overcome challenges and achieve long-term goals. Developing a growth mindset, which views failure as a part of the success process, can further improve grit and academic resilience. Rational Emotive Behavior Therapy counseling has been shown to boost grit and academic resilience. This study emphasizes the importance of training in academic resilience through REBT to support student success.